"Emissaries of Death and Destruction": Reading the Child-as-Killer in We Need to Talk about Kevin and Sharp Objects. Issue 4 (8th August 2019) - Miller, Alyson
ABSTRACT: Monstrous children possess "a unique power as horrific figures", able to generate disturbances that are as disquieting as they are enthralling. Focusing on Lionel Shriver's We Need to Talk About Kevin and Gillian Flynn's Sharp Objects, this paper examines how representations of children-who-kill dislocate mythologies of childhood to reveal anxieties about the threat of monstrous women to patriarchy. As David Sullivan and Jeff Greenberg argue via Kristeva, the monstrous child evokes a fear of the disruptive potential of the archaic mother (116), a reading in line with Karen J. Renner's discussion of how "monstrous births" disclose a cultural fixation on women as sites of loss and corruption. Moreover, in a complication of perceptions of the child as a symbol of futurity, the child-who-kills resists binaries of innocence and sin to expose cultural scripts which define the "real" as little more than "a hideous social mask". Exploring the monstrous child "within the intricate matrix of relations" in which it is produced reveals, this paper argues, a series of concerns about the symbolism (and sanctity) of the child and childhood per se, as well as deep-seated fears about the maintenance of normative culture more broadly.